Missed initial appointments at an outpatient forensic psychiatric clinic - Daniels, Melissa; Jung, Sandy (My University, 2009)
Non-attendance at first appointments is a significant problem in both the health and mental health care systems, and much of the research that has aimed to identify possible predictors of initial appointment, non-attendance at general treatment facilities have often provided contradictory and inconclusive results. This retrospective study reviewed the charts of patients who were referred to an outpatient forensic psychiatric clinic over a two-year period and identified a subset of patient- and clinic-related factors that have previously been identified in the literature to be associated with non-attendance. Of the 1630 charts reviewed, only 71.7% of patients attended their initial appointment. The findings indicated that forensic patients who were older and faced consequences related to sentencing were most likely to attend their initial appointments. The potential to improve attendance and subsequent treatment by identifying common factors that contribute to missing initial appointments is discussed, along with implications for increased efficiency of service delivery.
Keywords: psychiatric; forensic; outpatient; attendance; forensic setting; forensic psychiatry; forensic mental health